Handbook of research on school violence in American K-12 education - Crews, Gordon A. (IGI Global, 2019)
"This book examines the most frightening and challenging form of juvenile violence, the K-12 school violence perpetrator, as separate from all other forms of school and public offenders. It separates school violence perpetrators into a more concise types such as: traditional school violence perpetrators, gang-related school violence perpetrators, and non-school associated mentally ill school violence perpetrators"- Resumé vydavatel
Keywords: násilí ve škole -- Spojené státy americké; prevence (sociální problémy) -- Spojené státy americké; školy -- Spojené státy americké; school violence -- United States; prevention (social problems) -- United States; schools -- United States; elektronické knihy; příručky; electronic books; handbooks and manuals